Treatment of refractory partial seizures: preliminary results of a controlled study. - Holder LK; Wernicke JF; Tarver WB (Pacing & Clinical Electrophysiology, 1992)
Vagus nerve stimulation for the treatment of epilepsy has been studied in medically refractory patients with partial seizures in a randomized, blinded, parallel study. After a 3-month baseline period. the patients were implanted with the Neurocybernetic Prasthesis (NCP) system consisting of the NCP Generator and the Bipolar Vagal Stimulation Lead. Two stimulation paradigms were used. HIGH, which delivers what is considered to be optimal stimulation parameters and LOW, which is considered to be less or noneffective. The system and vagus nerve stimulation were well tolerated and few adverse events have been attributed to either. One patient experienced a period of direct current to the nerve due to a generator malfunction. This resulted in paralysis of the left vocal cord. Efficacy analysis on the first 37 patients to complete the controlled portion of the study has shown that the patients in the HIGH group experienced a mean reduction in seizure frequency of 33.3% and patients in the LOW group experienced a mean reduction in seizure frequency of 8.4%. The difference between the groups is statistically significant with a P value of 0.025. Analysis of seizure duration and intensity does not show any significant change. Ratings of the patient's overall condition by the patient, investigator, and companion as a measurement of 'quality of life' also show improvement in the HIGH group. The results of this interim study demonstrate that vagus nerve stimulation is a safe and effective method of treating partial epileptic seizures.